Influence of Levels of Metabolisable Protein in the Ration on Nutrient Utilization and Lactation Performance in Murrah Buffaloes - Sediqi, Jawid; Chaudhari, Alkesh; Tyagi, Nitin; Kumar, Sachin; Malhotra, Ravinder; Datt, Chander; Tyagi, A.K. (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to ascertain the effects of feeding varying levels of metabolisable protein on the nutrient utilization and production performance in Murrah buffaloes. Sixteen Murrah buffaloes in advanced stage of pregnancy (40-50 d before parturition) were divided into 3 groups on the basis of most probable production ability (MPPA) and lactation number. Duration of feeding trial was 130 days (40 days pre-partum to 90 days post-partum period. The animals were fed 3 different diets as low metabolizable protein (LMP), medium metabolizable protein (MMP) and high metabolizable protein (HMP) at MP levels of 85, 100 and 115% of ICAR (2013) recommendations, respectively, however, the diets had similar metabolisable energy (ME) content. The intakes of DM, ME and TDN were similar in all the experimental groups. The CP and MP intakes before and after calving were higher (P